Odpowiedzi

2010-01-08T15:56:28+01:00
A)
8x+5=7x
8x - 7x = -5
x = -5
spr. L(-5)= 8*(-5 ) + 5 =- 40+5 = -35
P(5) = 7*(-5) = -35
L(-5) = P(-5)
b)
7n+2=6n-3
7n - 6n = -3 -2
n = -5
L(-5) = 7*(-5) + 2 = -35 +2 = -33
P(-5) = 6*(-5) -3 = -30 -3 = -33
L(-5) = P(-5)

c)
-x+25=2x-2
-x -2x = -2 -25
-3x = -27
x = (-27) : (-3)= 9
x = 9
L(9) = -9 + 25 = 16
P(9) = 2*9 -2= 18 -2 = 16
L(9)= P(9)

d)
-9z-7=-z-6
-9z +z = -6 +7
-8z = 1
z = -1/8
L(-1/8 ) = (-9)*(-1/8) -7 = 9/8 - 56/8 = -47/8 = -5 i 7/8
P(-1/8) = -(-1/8) -6 = 1/8 -6 = -5i 7/8
L
e)
25m-3=24m-4
25m -24m = -4 +3
m = -1
L(-1) = 25*(-1) -3 = -25 -3 = -28
P(-1) = 24*(-1) -4 = -24 -4 = -28
P(-1) = L(-1)


f)
-s+15=4s-14
-s -4s = -14 -15
-5s = -29
s = (-29) : (-5) = 29/5
s = 29/5
L(29/5)= -29/5 + 15 = -5,8 + 15= 9,2
P(29/5) = 4*29/5 - 14 = 23,2 - 14 = 9,2
L(29/5) = P(29/5)


g)
17y+28=19y+27
17y - 19y = 27 -28
-2y = -1
y = (-1) : (-2) = 1/2
y = 1/2

L(1/2) = 17*1/2 + 28 = 8,5 = 28 = 36,5
P(1/2) = 19*1/2 + 27 = 9,5 + 27 = 36,5
l(1/2) = P(1/2)


h)
8k-19=-8k+19
8k +8k = 19 +19
16k = 38
k = 38 : 16
k = 19/8

L(19/8)= 8*19/8 - 19 = 19 - 19 = 0
P(19/8) = -8*19/8 + 19 = -19 + 19 = 0
L(19/8) = P(19/8)
2010-01-08T16:10:50+01:00
A)8x+5=7x / -8x
5 = -x / *(-1)
-5= x
x = -5
spr. 8 * (-5) + 5 = 7 * (-5)
-40 + 5 = -35
-35 = -35
b)7n+2=6n-3 / -6n / -2
n = -5
spr. 7 * (-5) +2 = 6 * (-5) - 3
-35 + 2 = -30 -3
-33 = -33
c)-x+25=2x-2 / +x /+2
27 = 3x / :3
9 = x
spr. -9+25 = 2*9 - 2
16 = 18 - 2
16 = 16
d)-9z-7=+-z-6
-9z-7=-z-6 / +7 / +z
-8z = 1 /:(-8)
z= - 1/8
spr. -9 * (-1/8) -7 = - (-1/8) - 6
1,125 - 7 = 0,125 - 6
-5,875 = -5,875
e)25m-3=24m-4 /-24m /+3
m = -1
spr. 25 * (-1) -3 = 24 * (-1) - 4
-25 -3 = -24 - 4
-28 = -28
f)-s+15=4s-14 /+s / +14
29 = 5s /:5
5,8 = s
s = 5,8
spr. -5,8 +15 = 4 * 5,8 - 14
9,2 = 23,2 - 14
9,2 = 9,2
g)17y+28=19y+27 / -17y /-27
1 = 2y / :2
0,5 = y
spr. 17 * 0,5 + 28= 19 * 0,5 + 27
8,5 + 28 = 9,5 + 27
36,5 = 36,5
h)8k-19=-8k+19 / + 8k / +19
16k = 38 / :16
k = 2,375
spr. 8 * 2,375 - 19 = -8 * 2,375 + 19
19 - 19 = -19 + 19
0 = 0